A Descriptive Study of Code Switching and Code Mixing Found in Aku Juga Tak Sempurna Episode on Perspektif Metro TV - Lusy Nur Indah Sari; Sutami Dwi Lestari; Arin Inayah (LUNAR, 2021)
Code switching and code mixing are phenomenon of bilingualism that are used in speech community. The goals of this research were to identify the types, to find out the most dominant type, and to analyze the reasons focused on code switching and code mixing found in Aku Juga Tak Sempurna episode on Perspektif Metro TV. This research used descriptive qualitative method. The data were classified based on Hoffman theory. Then, converting the number of types of code switching and code mixing by using Walizer formula. The analyzed method followed Mile and Huberman. The classifications of code switching occured 79 times, including: 70 data (88,6 %) of inter sentential switching, 7 data (8,8 %) of emblematic switching, and 2 data (2,5 %) of establishing continuity with the previous speaker. So the most dominant type of code switching is inter sentential switching. Moreover, the classification of code mixing occured 150 times, including: 120 data (80 %) of intra sentential mixing, 23 data (15,3 %) of intra lexical mixing, and 7 data (4,6 %) of involving a change of pronunciation. So the most dominant type of code mixing is inter sentential mixing. Then, the highest reason showed talking about a particular topic were 168 data. The intention of clarifying the speech content for interlocutor and expressing group identity had the same result, they reached 16 data. Showing empathy about something were 11 data. Quoting somebody else, interjection, and repetition used for clarification had the same result, they reached 6 data.